The correlation between laboratory skills frequency and the result of intranatal care practicum of midwifery program students of health faculty in Universitas Muhammadiyah Banjarmasin - Afiatun Rahmah; Rizki Amalia; Nelly Mariati (Universitas 'Aisyiyah Yogyakarta, 2019)
Based on IDHS Survey in 2012, the average Maternal Mortality Rate (MMR) was recorded at 359/100,000 live births. The average mortality rate was much higher compared to the results of IDHS survey in 2007 which was reached 228/100,000 live births. World health organization (WHO) in 2000s introduced Intranatal Care to prevent complications in childbirth. Intranatal care then was introduced to the student through university subject, in which 40% was theory and 60% was laboratory clinic practicum. This research aimed to determine the correlation between laboratory skills frequency and the result of intranatal care practicum of midwifery program students of health faculty in Universitas Muhammadiyah Banjarmasin. Methods: This research was quantitative study using descriptive analytic method with cross sectional approach. Sampling technique used was total sampling. The data were collected using secondary data which was presented in the form of data, tables, diagrams, or research topics by using Chi Square test with 95% significance level of 5,991. 32 (37,2%) respondents with 5 times of lab skill frequency showed 75 test scores, while 51 out of 54 (59,3%) respondents who had ≥5 lab skill frequency had ≥ 75 exam scores. Statistical analysis using Chi Square showed the value of p=0,000, which means that there was a correlation between lab skill frequency and the results of the practical test. Conclusion: It can be concluded that improving learning activities in the laboratory will improve students' practical abilities